Patterns of alpha and beta diversity of epigean arthropods at contrasting land-uses of an oceanic island (Terceira, Azores) - Cardoso, Pedro (2010)
"[…]. To study the effect of land-use change in biological communities it is necessary to understand how are the different components of diversity distributed in space. Diversity has long been separated into different components according to the phenomena that interest ecologists (Whittaker, 1960, 1972): i) local species richness, i.e., alpha (community) diversity that measures the species richness of a local assemblage; ii) beta diversity, the degree of difference between communities (Whittaker et al., 2001), that measures turnover of species between communities and; iii) gamma (regional) diversity, which can be considered an equivalent to alpha diversity on a larger scale, but reflects the allopatric distribution of related taxa. Alpha diversity, of which species richness is just the most visible measure, is perhaps the most studied aspect of diversity. However, probably more important than knowing how many species live in a site at a given time, it is to know what species are these. In islands, where the introduction of non-indigenous species is one of the major threats to indigenous species (Borges et al., 2006; Martín et al., 2008), especially endemics, this question is even more significant. Even if man-made habitats are species rich, they may be empty of species considered as conservation priority and abundant in exotic species (Cardoso et al. 2009a). […]" (da Introdução)